GAMBARAN PENGELOLAAN SURAT MENYURAT DI KANTOR DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI NUSA TENGGARA BARAT TAHUN 2024 - Sapitri, Liza; Lale Ajeng Khalifatun Wardani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
Correspondence management is an essential part of supporting the smooth operation of administrative activities in an institution, including in the Office of the Education and Culture Department of West Nusa Tenggara Province. This study aims to provide a comprehensive description of the management process of incoming and outgoing mail, including receipt, review, recording, disposition, distribution, and follow-up. The method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results show that correspondence management is carried out using both manual and digital systems, but it is still dominated by the manual system through the use of logbooks and control cards. The correspondence recording process utilizes a correspondence management system to optimize storage space and facilitate document retrieval. Some challenges were identified in the distribution process, such as incorrect recipient addresses and incomplete contact information. Each stage of correspondence management is carried out systematically by the administrative division, with the disposition process handled by the Head of Department and follow-up actions by each relevant division. This study recommends improving the use of digital systems and conducting regular staff training to enhance the efficiency of correspondence management